Investigation on the Tensile Behavior and Morphology Evolution of Isotactic Polypropylene Films Polymerized with Different Ziegler–Natta Catalysts. Issue 1 (21st August 2015) - Kang, Jian; Li, Xiaodan; Xiong, Bijin; Liu, Dongming; Chen, Jinyao; Yang, Feng; Cao, Ya; Xiang, Ming
ABSTRACT: Stereodefect distribution is very important in determining the morphology and properties of isotactic polypropylene (iPP). In this study, two iPPs (PP‐A and PP‐B) with different uniformities of stereodefect distribution were prepared. The tensile behavior and morphology evolution of their cast films were studied. The morphology study of the cast films showed that compared with PP‐B, PP‐A with less uniform distribution of stereodefects has smaller spherulites and spheruilitic boundaries and higher degree of crystallinity. In uniaxial tensile measurements, PP‐A exhibited higher yield strength and lower elongation at break. When strain was 500%, PP‐A exhibits totally transparent appearance and highly oriented structures without cavities, whereas PP‐B shows opaque appearance and mass of both nanometer‐ and micrometer‐sized cavities. Moreover, calculation of rigid amorphous fraction (RAF) indicated that PP‐B cast film has a higher amount of RAF, which might be the reason for the different morphology evolutions and tensile behaviors of the samples.